Tribute to Eugene Gendlin, Psychotherapist, Humanist and Researcher, on the Occasion of his Death - Carlos Alemany Briz; Enrique Aguilar Peñas (Miscelánea Comillas, 2019)
A vital balance about Eugene T. Gendlin, philosopher and psychotherapist, professor at the University of Chicago, creator of the «Focusing Oriented Therapy» (FOT) school, is made. The most outstanding concepts that this autor addresses are experiencing, felt- sense, focusing and Thinking at the Edge (PDB/ TAE). The tribute includes a selection of research carried out over the last 20 years, sorted by fields of application. This homage is completed with the Spanish adaptation of the Focusing Manner Scale (Aoki and Ikemi, 2013).